Factors associated with non-adherence to Antiretroviral Therapy (ART) in adult individuals living with Human Immunodeficiency Virus (HIV) in Mogadishu, Somalia: A hospital-based cross-sectional study - Abdirahman Khalif Mohamud; Bashiru Garba; Najib Isse Dirie; Pamornsri Inchon; Maryan Abdullahi Sh Nur; Jamal Hassan Mohamoud; Mohamed Mustaf Ahmed (PLoS ONE, 2025)
Background Antiretroviral Therapy is an effective method against HIV, reducing mortality and opportunistic infections. In Somalia, high rates of these infections and low adherence to therapy have been reported. However, factors contributing to non-adherence remain unidentified. Therefore, The study aims to assess the magnitude of antiretroviral therapy non-adherence and identify associated factors for individuals living with HIV in Mogadishu, Somalia. Methodology A hospital-based cross-sectional study was conducted using a questionnaire containing socio-demographic, behavioral, familial, psychosocial, clinical, and laboratory characteristics. Antiretroviral Therapy adherence was assessed by quantifying the number of prescribed pills taken in the past month. Those who adhered to ≥95% of the prescribed Antiretroviral Therapy drugs were considered adherent to Antiretroviral Therapy. Logistic regression was used to identify factors associated with Antiretroviral Therapy non-adherence at significance levels of p < 0.05. Results Out of 453 participants, the magnitude of non-adherence to ART among people living with HIV in Mogadishu, Somalia, was 138 (30.5%) with its 95% CI: 26.3–34.9. The predominant reasons for missing ART were forgetting (7.3%), transportation issues (5.5%), side effects and being busy with other commitments (4.4%), stigma (3.8%), and ART facilities being distant from home (2.6%). In multivariable logistic regression, living alone (AOR=1.81, 95%CI:1.182–2.782), perceived stigma (AOR=3.19, 95%CI:1.784–5.720), smoking cigarettes (AOR=2.96, 95%CI:1.759–5.003), and living with a co-morbid chronic disease (AOR=1.80, 95%CI:1.155–2.813) were factors associated with ART non-adherence among people living with HIV in Mogadishu, Somalia. Conclusion Individuals living with HIV in Mogadishu, Somalia suffer sub-optimal adherence to ART. Priority should be given to strategically addressing the needs of those living alone and individuals with co-morbid chronic conditions, eliminating HIV stigma, and discouraging substance abuse.